Dielectric and kinetic comparison of APO-BMI grades. (November 2018) - Daily, Connor; Torres, Sabrina MW; Robison, Thomas W; Bowler, Nicola
Low-density, high-strength, and high-temperature foams are recently finding new structural applications in the aerospace sector. In many instances, these foams are comprised of a thermosetting polymer resin incorporating dispersed microballoons, of a variety of materials, to achieve low mass density and other behaviors. Bismaleimide (BMI) is a thermosetting resin that is being used in these applications, in a variety of formulations. In this study, BMI is combined with Apocure-601 (APO). While a purified grade of the APO-BMI resin is achievable, an unpurified, production-ready grade is regularly utilized. To understand the performance and aging mechanisms of the two grades, and differences between them, they have been characterized by broadband dielectric spectroscopy over frequency range of 10 −1 Hz to 10 6 Hz and temperature range of −140°C to approximately 300°C. Additionally, the thermogravimetric analysis (TGA) coupled with an evolved gas characterization technique (mass spectrometry) has been applied. Results show that impurities in the production grade APO-BMI lead to significant differences in the dielectric alpha-relaxation, in comparison to those measured on the purified APO-BMI resin. Additionally, kinetic models based on TGA results were developed to describe the thermo-oxidative degradation of the two materials. Using these models, life predictions based on both isothermal and cyclic exposure to temperatures up to 300°C and durations up to 25 h have shown significantly more higher mass loss for production grade material compared to the purified APO-BMI. Additional use of this model for specific conditions may provide beneficial information to the aerospace industry.